2013
DOI: 10.5195/ijt.2013.6125
|View full text |Cite
|
Sign up to set email alerts
|

A Telephone-based Physiotherapy Intervention for Patients with Osteoarthritis of the Knee

Abstract: This study assessed the effects of a 6-week telephone based intervention on the pain intensity and physical function of patients with knee osteoarthritis (OA), and compared the results to physiotherapy conducted in the clinic. Fifty randomly selected patients with knee OA were assigned to one of two treatment groups: a clinic group (CG) and a tele-physiotherapy group (TG). The CG received thrice-weekly physiotherapist administered osteoarthritis-specific exercises in the clinic for six weeks. The TG received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 13 publications
6
102
0
1
Order By: Relevance
“…All interventions focused on supporting self-management and providing education in addition to a range of intervention targets, for example physical activity (see Table 1 for details). A total of 17 studies assessed pain intensity ( Weinberger et al, 1989 ; Mazzuca et al, 1997 ; Thomas et al, 2002 ; Buhrman et al, 2004 ; Hughes et al, 2010 ; Allen et al, 2010 , 2016 , 2017 ; Odole & Ojo, 2013 ; Cuperus et al, 2015 ; De Rezende et al, 2016 ; Bennell et al, 2017 ; Gialanella et al, 2017 ; Li et al, 2017 ; O’Brien et al, 2018 ; Rutledge et al, 2018 ; Williams et al, 2018 ) and 21 studies assessed a disability outcome ( Weinberger et al, 1989 ; Maisiak, Austin & Heck, 1996 ; Mazzuca et al, 1997 ; Burks, 2001 ; Damush et al, 2003 ; Blixen et al, 2004 ; Hughes et al, 2010 ; Allen et al, 2010 , 2016 , 2017 ; Iles et al, 2011 ; Odole & Ojo, 2013 ; Cuperus et al, 2015 ; De Rezende et al, 2016 ; Bennell et al, 2017 ; Gialanella et al, 2017 ; Li et al, 2017 ; O’Brien et al, 2018 ; Rutledge et al, 2018 ; Goode et al, 2018 ; Williams et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All interventions focused on supporting self-management and providing education in addition to a range of intervention targets, for example physical activity (see Table 1 for details). A total of 17 studies assessed pain intensity ( Weinberger et al, 1989 ; Mazzuca et al, 1997 ; Thomas et al, 2002 ; Buhrman et al, 2004 ; Hughes et al, 2010 ; Allen et al, 2010 , 2016 , 2017 ; Odole & Ojo, 2013 ; Cuperus et al, 2015 ; De Rezende et al, 2016 ; Bennell et al, 2017 ; Gialanella et al, 2017 ; Li et al, 2017 ; O’Brien et al, 2018 ; Rutledge et al, 2018 ; Williams et al, 2018 ) and 21 studies assessed a disability outcome ( Weinberger et al, 1989 ; Maisiak, Austin & Heck, 1996 ; Mazzuca et al, 1997 ; Burks, 2001 ; Damush et al, 2003 ; Blixen et al, 2004 ; Hughes et al, 2010 ; Allen et al, 2010 , 2016 , 2017 ; Iles et al, 2011 ; Odole & Ojo, 2013 ; Cuperus et al, 2015 ; De Rezende et al, 2016 ; Bennell et al, 2017 ; Gialanella et al, 2017 ; Li et al, 2017 ; O’Brien et al, 2018 ; Rutledge et al, 2018 ; Goode et al, 2018 ; Williams et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…No subgroup analyses were possible for any comparative effectiveness comparisons ( Table 2 ). A further two studies ( Hughes et al, 2010 ; Odole & Ojo, 2013 ) were not included in the meta-analysis due to dissimilar intervention components or did not report sufficient data (e.g. means at follow-up not reported).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telephone interventions for knee OA have been studied previously 41. Only two studies have involved physiotherapist consultations, evaluating telephone calls to follow-up in-person physiotherapist consultation(s) 42 43. Our trial is unique because our physiotherapists prescribed strengthening and physical activity entirely over the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…Stability of the knee joint which is enhanced by increased quadriceps muscle strength following resistance exercises has been opined to improve function in patients with OA 59 . Similarly, Alnahdi et al 64 in a review of literature also identified muscle strength especially quadriceps as a major determinant of both performance -based and self-reported physical function and further submitted that exercise therapy, including global and targeted resistance training, is 40,53,65,66 . The similarity between the findings of these researchers and that of the present study may be attributed to significant pain reduction observed in present study which was also reported by these authors; a significant inverse relationship between pain and physical function has been previously reported in literature 67 .…”
Section: Discussion Effects Of Open Closed and Combined Chain Exercimentioning
confidence: 99%